Bone Health Status among Thalassemia Children. - Yeo, Pei Sien; Noor Aini Mohd Yusoff,; Suzana Shahar,; Roslee Rajikan, (Universiti Kebangsaan Malaysia, 2013)
Low bone mineral density is a significant problem in children with Thalassemia which may lead to increased risk for fragility fractures and suboptimal peak bone mass. This cross-sectional study was conducted to determine the bone health status of Thalassemia children Universiti Kebangsaan Malaysia Medical Centre and Paediatrics Insititute Kuala Lumpur Hospital.